Kuasai rintas: penulisan ringkasan bahasa Melayu yang lengkap / Gladys Sebi Entigar ... [et al.] - Entigar, Gladys Sebi; Noor Azam, Noor Haty; Mohd Jamil, Milfadzhilah; Ahmed, Roziana (2021)
Kuasai Rintas is an additional exercise book to master the method of writing shorthand in Malay Language. It is a method of writing system by means of abbreviations to common words, used especially for taking dictation. Kuasai Rintas is created as a supplementary of the available textbook entitled Rintas. Rintas shorthand skills were introduced by Rufiah Rafiee and Mornizan Yahya (2001). Both authors are Senior Lecturers from the Faculty of Office Management and Technology, Universiti Teknologi Mara (UiTM) Malaysia. Kuasai Rintas is innovated with more attractive features with variety of colorful images, simple words and articles which means it can be of interest for a person to learn Rintas shorthand skills. Nowadays, learning Rintas shorthand skills are relevant parallel with the advancement in technology in which these skills often used in writing and sending short messages via mobile phone, taking minutes and phone messages in the office and others daily use to help the executives and the secretaries to work conveniently. In a nutshell, Kuasai Rintas is suitable for everyone who is wishing to improve their shorthand skills. This is because Kuasai Rintas provides specific of learning guidelines and the basic principles or commands that are easier to understand. Furthermore, Kuasai Rintas also provides numerous commands using colors and images that match the words with the pictures whereby these methods will help to improve memory and speed up the process of understanding Rintas. In line with the working system that requires a short time, efficiency and quality, Rintas shorthand skills are very useful to the executives and secretaries from either in the government or private sectors. Lastly, in order to reinforce these shorthand skills, Kuasai Rintas could become an additional academic materials and references for the University and Vocational School where it can be learned and practiced comprehensively.